Flow-metabolism uncoupling in patients with asymptomatic unilateral carotid artery stenosis assessed by multi-modal magnetic resonance imaging. Issue 11 (November 2019) - Göttler, Jens; Kaczmarz, Stephan; Kallmayer, Michael; Wustrow, Isabel; Eckstein, Hans-Henning; Zimmer, Claus; Sorg, Christian; Preibisch, Christine; Hyder, Fahmeed
Oxygen extraction (OEF), oxidative metabolism (CMRO2 ), and blood flow (CBF) in the brain, as well as the coupling between CMRO2 and CBF due to cerebral autoregulation are fundamental to brain's health. We used a clinically feasible MRI protocol to assess impairments of these parameters in the perfusion territories of stenosed carotid arteries. Twenty-nine patients with unilateral high-grade carotid stenosis and thirty age-matched healthy controls underwent multi-modal MRI scans. Pseudo-continuous arterial spin labeling (pCASL) yielded absolute CBF, whereas multi-parametric quantitative blood oxygenation level dependent (mqBOLD) modeling allowed imaging of relative OEF and CMRO2 . Both CBF and CMRO2 were significantly reduced in the stenosed territory compared to the contralateral side, while OEF was evenly distributed across both hemispheres similarly in patients and controls. The CMRO2 -CBF coupling was significantly different between both hemispheres in patients, i.e. significant interhemispheric flow-metabolism uncoupling was observed in patients compared to controls. Given that CBF and CMRO2 are intimately linked to brain function in health and disease, the proposed easily applicable MRI protocol of pCASL and mqBOLD imaging might serve as a valuable tool for early diagnosis of potentially harmful cerebral hemodynamic and metabolic states with the final aim to select clinically asymptomatic patients who would benefit from carotid revascularization therapy.